2006
DOI: 10.12927/hcq.2013.18376
|View full text |Cite
|
Sign up to set email alerts
|

Is Your Patient Ready for Transport? Developing an ICU Patient Transport Decision Scorecard

Abstract: Transport of patients from the intensive care unit (ICU) to another area of the hospital can pose serious risks if the patient has not been assessed prior to transport. Recently, the Department of Critical Care Medicine, Calgary Health Region, experienced two adverse events during transport. A subgroup of the Department's Patient Safety and Adverse Events team developed an ICU patient transport decision scorecard. This tool was tested through Plan-Do-Study-Act cycles and further revised using human factors pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…24 The AHRQ guidelines emphasize training staff about handoffs, troubleshooting equipment, how to get help, and competency. In addition, the AHRQ supports development of a tool, such as a scoring system for patients' acuity, 12,31 for pretransport assessment to evaluate patients' stability for travel.…”
Section: Guidelines For Intrahospital Transportmentioning
confidence: 99%
See 3 more Smart Citations
“…24 The AHRQ guidelines emphasize training staff about handoffs, troubleshooting equipment, how to get help, and competency. In addition, the AHRQ supports development of a tool, such as a scoring system for patients' acuity, 12,31 for pretransport assessment to evaluate patients' stability for travel.…”
Section: Guidelines For Intrahospital Transportmentioning
confidence: 99%
“…Benefit must outweigh risk, with the transport in the best interest of the patient. 3,6,[11][12][13][14]31,33 In a review of transport literature published in 1999, Waydhas et al 2 reported a change in management in 40% to 50% of patients transported for diagnostic procedures, "indicating a good risk/benefit ratio." These older data are not supplemented by more recent studies because little recent research has been conducted.…”
Section: Whymentioning
confidence: 99%
See 2 more Smart Citations
“…Esmail et al 10 published an ICU patient transport decision scorecard developed for a health system in Calgary, Canada. This tool includes a…”
Section: Intrafacility Transport Checklistsmentioning
confidence: 99%